Biological material collection to advance translational research and treatment of children with CNS tumours: position paper from the SIOPE Brain Tumour Group. Issue 8 (August 2018) - Rutkowski, Stefan; Modena, Piergiorgio; Williamson, Daniel; Kerl, Kornelius; Nysom, Karsten; Pizer, Barry; Bartels, Ute; Puget, Stephanie; Doz, François; Michalski, Antony; von Hoff, Katja; Chevignard, Mathilde; et al.
Summary: Paediatric CNS tumours are the most common cause of childhood cancer-related morbidity and mortality, and improvements in their diagnosis and treatment are needed. New genetic and epigenetic information about paediatric CNS tumours is transforming the field dramatically. For most paediatric CNS tumour entities, subgroups with distinct biological characteristics have been identified, and these characteristics are increasingly used to facilitate accurate diagnoses and therapeutic recommendations. Future treatments will be further tailored to specific molecular subtypes of disease, specific tumour predisposition syndromes, and other biological criteria. Successful biomaterial collection is a key requirement for the application of contemporary methodologies for the validation of candidate prognostic factors, the discovery of new biomarkers, the establishment of appropriate preclinical research models for targeted agents, a quicker clinical implementation of precision medicine, and for other therapeutic uses (eg, for immunotherapies). However, deficits in organisational structures and interdisciplinary cooperation are impeding the collection of high-quality biomaterial from CNS tumours in most centres. Practical, legal, and ethical guidelines for consent, storage, material transfer, biobanking, data sharing, and funding should be established by research consortia and local institutions to allow optimal collection of primary and subsequent tumour tissue, body fluids, and normal tissue. Procedures for the collection and storage of biomaterials and related data should be implemented according to the individual and organisational structures of the local institutions.